Ezequiel Urviola. Basta con que haya vivido - ESPEZUA SALMON, BORIS GILMAR (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
In the present work, we intend to address the transition of Ezequiel Urviola, as a unique character who ontologically wanted to be Indian, in a process of transculturation and decolonization and that both his commitment to the Andean world, as well as the causes of his discrimination and his struggles for his vindication have served him to constitute a beacon in the painful process of visibility and redemption of the indigenous compatriot in our country who still has many historical debts to cancel, many wounds to heal, so that we can prefigure a diverse country, intercultural and definitely that it is a legitimate and identitary nation with equal fundamental rights.